Comparative in vitro antibacterial activities study of some mucoadhesive polymeric suspensions containing fluoroquinolones - Chandra Kanti Chakraborti, Subhashree Sahoo, Pradipta Kumar Behera, Anjulata Manjari Sahoo (Journal of Applied Pharmaceutical Science)
To study in vitro antibacterial activities of mucoadhesive suspensions containing Norfloxacin, Ciprofloxacin and Ofloxacin, three different formulations of each drug were prepared by using three polymers, such as Hydroxypropyl methylcellulose (HPMC), Carbapol934 (C934) and Carbapol940 (C940), along with some common ingredients (bases). For the antibacterial activities study of the samples, agar well diffusion method was performed taking Staphylococcus aureus (ATCC 25923), Bacillus subtilis and Escherichia coli (ATCC 25922). Considering the overall antibacterial activities, it could be mentioned that HPMC containing formulations were superior to others in most of the cases. Amongst C934 and C940 containing suspensions, the former was more potent than the later. Antibacterial activities of most of the formulations were either more effective or similar to those of corresponding drugs in water against the strains used in the study. Only few formulations were inferior to the corresponding drugs in water. Ciprofloxacin in citrate buffer was not better than Ciprofloxacin containing suspensions. Samples like both marketed suspensions and discs of different drugs were inferior to all the formulations and corresponding drugs in water/Ciprofloxacin in citrate buffer. The negative controls of the study, i.e., the different bases, distilled water and citrate buffer did not show any antibacterial activity.
Keywords: Norfloxacin, Ciprofloxacin, Ofloxacin, HPMC, C934, C940